Early sublingual microcirculation changes in patients with septic shock at different altitudes - HE Zongzhao, WANG Hao*, GUO Litao, MA Siqing, XIANG Hui, ZHENG Xing (Zhongguo linchuang yanjiu)
Objective To observe the changes of early sublingual microcirculation in patients with septic shock at different altitudes, and to provide reference for clinical treatment of patients with septic shock at high altitude. Methods From September 2021 to March 2023, patients with septic shock at high altitude (Xining, 28 cases) and at low altitude (Wuhan, 26 cases) were selected as study subjects in the Department of Intensive Care Medicine of Qinghai Provincial People's Hospital and Zhongnan Hospital of Wuhan University. The basal data, blood cell counts, inflammation indexes, and coagulation function indexes ［prothrombin time (PT), thrombin time (TT), and international normalized ratio (INR)］ were recoded. The sidestream dark field (SDF) monitoring technique was used to monitor sublingual microcirculation indexes ［total vascular density (TVD), perfusion vascular density (PVD), proportion of perfused vessels (PPV), microfluidic flow index (MFI), and heterogeneity index (HI)］. The changes of sublingual microcirculation in patients at different altitudes were compared. Results There was no statistically significant difference in the comparison of basic information, inflammation indexes and INR between patients with septic shock in the two regions (P＞0.05). However, the PT［19.65 (16.80, 31.50) s vs 14.60 (12.92, 18.65) s］and TT ［20.45 (18.78, 23.18) s vs 15.65 (13.82, 19.55) s］ were significantly longer in the high-altitude region compared to the low-altitude region (P＜0.05). Compared with patients in low altitude, TVD［17.37 (13.61, 19.65) mm/mm2 vs 14.18 (13.10, 16.07) mm/mm2］ and HI［1.60 (0.55, 3.00) vs 0.71 (0.44, 1.05)］ were significantly higher, while PVD［3.29 (1.83,11.24) mm/mm2 vs 12.66 (9.39,14.87) mm/mm2］、PPV［22.55% (10.28%, 77.15%) vs 87.85% (72.02%, 94.65%)］, and MFI［0.87 (0.63, 1.95) vs 2.50 (2.24, 2.71)］ were significantly lower in high altitude region (P＜0.05). Conclusion The disturbance of sublingual microcirculation in patients with septic shock at high altitude is more pronounced compared to those at low altitude. Specifically, there is a significant reduction in PVD, PPV, and MFI, while the HI of perfusion distribution becomes more prominent.